The Influence of Service Quality, Product Quality, and Promotion on Purchase Decision at PT. Unikitz Bersatu Group Medan Branch - Steven Pratama Susanto; Melkyory Andronicus (Institute of Computer Science (IOCS), 2021)
This study aims to determine the effect of service quality, product quality, and promotion on purchase decision at PT. Unikitz Bersatu Group Medan Branch. This type of research is explanatory research. The research population that will be used in the study are all consumers who make purchases at the company in 2020, which are 2,319 consumers. Due to the large number of population, the sampling technique will be reduced by using the Slovin formula with an error tolerance level of 10% so that there are 96 respondents. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that service quality, product quality, and promotion partially or simultaneously have a positive and significant effect on purchase decision at PT. Unikitz Bersatu Group Medan Branch. Based on the results of this study, the implications for management are to further improve service quality, improve a better product quality, improve the promotion.